2014
DOI: 10.12659/msm.890879
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Clinical and Microbiological Variables in Patients with Type 1 Diabetes Mellitus and Periodontitis

Abstract: BackgroundThe aim of the study was to analyze how metabolic control of type 1 diabetes is related to clinical and microbiological periodontal parameters.Material/MethodsThe study involved 56 subjects aged from 19 to 50 years divided into 2 groups: healthy subjects (the H group), and diabetic (type 1 diabetes) patients with chronic untreated generalized periodontitis (the DM group). The glycosylated hemoglobin value (HbA1c) was determined using the UniCel DxC 800 SYNCHRON System (Beckman Coulter, USA), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…28 Additionally, it has been detected in higher abundance in patients with Type 1 diabetes mellitus. 29 …”
Section: Discussionmentioning
confidence: 99%
“…28 Additionally, it has been detected in higher abundance in patients with Type 1 diabetes mellitus. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on PCR technology also show a shift in microbial composition in DM (Aemaimanan, Amimanan, & Taweechaisupapong, 2013;Castrillon et al, 2015;Demmer et al, 2015;Merchant et al, 2014;Sakalauskiene et al, 2014). Furthermore, three of these studies demonstrated this shift only in poorly controlled diabetic patients (Aemaimanan et al, 2013;Merchant et al, 2014;Sakalauskiene et al, 2014). Still, the above data do not provide solid evidence of causal relationship between poorly controlled DM and periodontal microbial dysbiosis, and the available date derived from cross-sectional studies.…”
Section: Biological Plausibility Of Increase In Severity Of Periodomentioning
confidence: 97%
“…Recent studies that explored the possible association between the compositions of the periodontal flora in patients with diabetes using 16S rRNA Sequencing (Casarin et al, 2013;Zhou et al, 2013) found evidence which may indicate a difference in microbial composition in patients with diabetes mellitus (DM). Recent studies based on PCR technology also show a shift in microbial composition in DM (Aemaimanan, Amimanan, & Taweechaisupapong, 2013;Castrillon et al, 2015;Demmer et al, 2015;Merchant et al, 2014;Sakalauskiene et al, 2014). Furthermore, three of these studies demonstrated this shift only in poorly controlled diabetic patients (Aemaimanan et al, 2013;Merchant et al, 2014;Sakalauskiene et al, 2014).…”
Section: Biological Plausibility Of Increase In Severity Of Periodomentioning
confidence: 98%
“…E. corrodens , a Gram negative facultative anaerobic bacillus and allocated to the green complex, plays a presumably important role as an early colonizer as well [ 3 ]. It is also meant to be associated with the development of periodontitis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%